Direct synthesis of an anionic 13-vertex closo-cobaltacarborane cluster. Issue 42 (15th October 2019) - Maier, Thomas M.; Coburger, Peter; van Leest, Nicolaas P.; Hey-Hawkins, Evamarie; Wolf, Robert
Abstract : Reaction of 1, 2-bis(diphenylphosphino)- ortho -carborane (L ) with [K(thf)( Mes BIAN)Co(η 4 -cod)] (1, Mes BIAN = bis(mesityliminoacenaphthene)diimine, cod = 1, 5-cyclooctadiene) affords an anionic 13-vertex closo -cobaltacarborane cluster (2 ) in one step. Abstract : Reaction of 1, 2-bis(diphenylphosphino)- ortho -carborane (L ) with [K(thf)( Mes BIAN)Co(η 4 -cod)] (1, Mes BIAN = bis(mesityliminoace-naphthene)diimine, cod = 1, 5-cyclooctadiene) affords an anionic 13-vertex closo -cobaltacarborane cluster (2 ) in one step. The mechanism of this transformation has been studied by experimental and quantum chemical techniques, which suggest that a series of outer-sphere electron transfer and isomerisation processes occurs. This work shows that low-valent metalate anions are promising reagents for the synthesis of anionic metallacarborane clusters.